AI-Powered Governance: Exploring the Role of Artificial Intelligence in Shaping Public Service Innovation - Ngr. Putu Raka Novandra Asta; Vinto Rizalfi; Sun Wei (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid advancement of Artificial Intelligence (AI) has significantly transformed various sectors, including public governance. In the face of increasing demands for efficiency, transparency, and citizen-centric services, governments around the world are turning to AI to reimagine the structure and delivery of public services. Purpose. This research explores how AI technologies are being integrated into public governance systems to drive innovation, enhance administrative performance, and foster participatory governance. The objective of this study is to analyze the extent to which AI-powered tools contribute to the modernization of public service delivery and to identify the challenges and ethical considerations arising from this transformation. Method. This study employs a qualitative research approach using a systematic literature review method. A comprehensive analysis of academic articles, policy reports, and case studies was conducted, focusing on AI applications in public service innovation across multiple countries. Results. The results reveal that AI has played a pivotal role in automating administrative tasks, improving data-driven decision-making, and enabling predictive services. However, the implementation of AI also introduces concerns regarding algorithmic transparency, data privacy, and accountability. Conclusion. The study concludes that while AI holds immense potential to reshape public governance and stimulate service innovation, its success depends on the alignment of technological capabilities with inclusive policy frameworks and ethical standards. Future governance models must prioritize human oversight, regulatory compliance, and equitable access to ensure sustainable innovation.